2008
DOI: 10.1002/ldr.876
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi in degraded typical steppe of inner Mongolia

Abstract: Arbuscular mycorrhizal (AM) fungi may have some potential use in the restoration of degraded grassland through beneficial effects on plant growth and soil quality. A field investigation was conducted in three grassland sites of typical steppe in Inner Mongolia. The three plant communities, one of which was undegraded, one moderately degraded and the third severely degraded, were studied by collecting soil samples and samples of four plant species that occurred in all three sites. The percentage of root length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…Mycorrhizal species probably remain at the same root colonization levels in spite of changes in AMF community composition. Indeed, Tian et al (2009) reported that the AMF root colonization of four indicator plants did not decline in the grazed area, while the AMF species composition changed substantially with increasing grazing pressure in a typical steppe of Inner Mongolia. There are previous reports of Fig.…”
Section: Relationship Between Grazing and Root Colonization And Amf Cmentioning
confidence: 97%
See 3 more Smart Citations
“…Mycorrhizal species probably remain at the same root colonization levels in spite of changes in AMF community composition. Indeed, Tian et al (2009) reported that the AMF root colonization of four indicator plants did not decline in the grazed area, while the AMF species composition changed substantially with increasing grazing pressure in a typical steppe of Inner Mongolia. There are previous reports of Fig.…”
Section: Relationship Between Grazing and Root Colonization And Amf Cmentioning
confidence: 97%
“…The composition and abundance of AMF spore species varied among sites with different grazing pressures. Glomus was the dominant genus in the Reserve and grazed sites, as has been found in other arid and semiarid areas (Su and Guo 2007;Tian et al 2009 The characters of the AMF community differed among the sites with different grazing pressures (Table 1). There was higher spore density, AMF species richness and root colonization in the lightly and moderately grazed sites than in the other heavily grazed sites and the Reserve.…”
Section: Composition and Diversity Of Amf Communitymentioning
confidence: 98%
See 2 more Smart Citations
“…The P Olsen , AN and AK were positively correlated with the second axis, but the P Olsen had the higher degree of correlation with AMF distribution. Tian et al (2009) also reported that pH, C ox and P Olsen had severe influences on the distribution of AMF community. The results indicated that the soil environment modification caused by different SM practices should be a major factor impacting the AMF spore communities in citrus orchards.…”
Section: Results and Disscussionmentioning
confidence: 94%